2015
DOI: 10.1111/jfr3.12178
|View full text |Cite
|
Sign up to set email alerts
|

Development of an expert‐led GIS‐based approach for assessing the performance of river levees: the Digsure method and tool

Abstract: France and other regions around the world frequently undergo devastating flood events. Any failure of a flood protection structure can lead to human casualties and material damage. Unfortunately, such long linear structures are often poorly maintained and have shown repeated signs of weakness. Therefore, river levee management raises a number of substantial issues for the decision-makers responsible for ensuring maximum safety for the surrounding population at a reasonable management cost. The aim of the Digsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The proposed three different assessment methods are based on combining data, expert judgments, index based methods and empirical (physical and mathematical) models. Peyras [40], in contrast, develop methods that can assist levee safety using geographic information system (GIS). Levee safety is closely linked to levee technical condition, which is evaluated using numerous publications in the form of handbooks or guidelines (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…The proposed three different assessment methods are based on combining data, expert judgments, index based methods and empirical (physical and mathematical) models. Peyras [40], in contrast, develop methods that can assist levee safety using geographic information system (GIS). Levee safety is closely linked to levee technical condition, which is evaluated using numerous publications in the form of handbooks or guidelines (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…Progressive refinement of risk estimation and subsequent improvement of dike system management can be achieved by assessing existing knowledge gaps in order to better understand the impact of uncertainties within the risk analysis process. Recent research (e.g., Vuillet et al, 2016;Peyras et al, 2015;Gelder et al, 2008) has suggested different methods to deal with the uncertainty in the structural performance of dikes, e.g., subjective probabilities were used to characterise the uncertainty of input data, and Monte Carlo simulations were used to propagate the parameter uncertainty in dike failure scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the safety of levees is a major challenge for the managers of these structures in order to predict a risk of failure (Kolen et al, 2013). Moreover, many regulations require the evaluation of the reliability of structures in a probabilistic framework, in order to demonstrate levee failure risks (Ciria et al, 2013 ;Peyras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%